Out of the Dust : New and Selected Poems - Mirikitani, Janice (Book collections on Project MUSE., 2014)
Out of the Dust is a collection of new poems by activist, leader, poet, and editor Janice Mirikitani. After being named San Francisco's second Poet Laureate in 2000, this fifth book of poems from Mirikitani was written in response to the terrorist attacks on September 11, 2001. Drawing from her own background as a Sansei (third generation) Japanese American, Mirikitani reflects on the many ways we connect through the dust and our ability to rise and renew ourselves from this place. From the dust of the World Trade Center in New York to the retaliatory ashes of the dead in America's war in Afghanistan, the poems in this volume seek to explicate the connections of our humanity to the reactionary profiling of people of Middle Eastern descent and different ethnicities, comparing these choices to the incarceration of Japanese Americans during World War II. Mirikitani's poems cover topics about rape, incest, the continued struggle for justice and economic equality, and the poet's experiences throughout her 50-year career at Glide Foundation and Church in San Francisco, where she has helped to create groundbreaking programs for the poor, women and children, and those who are healing from sexual assault, violence and abuse. Though constructed from a depth of experiences with struggle, these poems also erupt in celebration of marriage, daughters, and the discovery of self through diversity.